2015
DOI: 10.1038/jcbfm.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Dampens Injury-Induced Microglial Motility

Abstract: Traumatic brain injury causes progressive brain atrophy and cognitive decline. Surprisingly, an early treatment with erythropoietin (EPO) prevents these consequences of secondary neurodegeneration, but the mechanisms have remained obscure. Here we show by advanced imaging and innovative analytical tools that recombinant human EPO, a clinically established and neuroprotective growth factor, dampens microglial activity, as visualized also in vivo by a strongly attenuated injury-induced cellular motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…The preparation and culture conditions of primary mouse oligodendrocytes and microglia are described in detail elsewhere (24)(25). In brief, oligodendrocytes were prepared from the forebrains of newborn P1-2 NMRI mice.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The preparation and culture conditions of primary mouse oligodendrocytes and microglia are described in detail elsewhere (24)(25). In brief, oligodendrocytes were prepared from the forebrains of newborn P1-2 NMRI mice.…”
Section: Cell Culturementioning
confidence: 99%
“…In addition, EPO and EPOR mRNA are expressed in brain tissue (21), and specific binding sites for EPO in the brain have been demonstrated in mouse and humans by means of radiolabeled EPO (22)(23). In cell culture, mRNA expression combined with functional assays, for example, altered phosphorylation of second messenger pathways induced by EPO in microglia, served to prove specific EPOR expression in the absence of reliable EPOR-AB (24).…”
mentioning
confidence: 99%
“…Iba-1 immunostatining is classically used to label microglia, however, we only analyzed microglia burden and it is possible that more complex inflammatory changes are not covered with our approach. Previous studies have shown that microglia express EPO receptors (Nagai et al, 2001) and that EPO may reduce motility, as an important feature of microglial pathological reaction to damage (Mitkovski et al, 2015), while promoting the polarization of microglia toward the protective M2 phenotype (Wei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Prominent general functions of Epo in the nervous system and in other non-hematopoietic tissues are protection from apoptosis, reduction of inflammatory responses and re-establishment of compromised functions by support of proliferation, migration and differentiation to compensate for lost or injured cells [ 12 ]. Concerning the nervous system more specifically, Epo has been demonstrated to be crucial for normal brain development [ 30 , 31 ], to act neuroprotectively after hypoxic/ischemic insults and glutamate excitotoxicity [ 28 , 32 ], to suppress neuroinflammatory processes including activation of microglia [ 33 , 34 ] and to promote regeneration after axonal damage [ 35 , 36 , 37 ]. Moreover, Epo enhanced cognitive performance and memory retrieval in healthy humans and patients affected by mood disorders or schizophrenia [ 38 , 39 , 40 , 41 , 42 , 43 ] paralleling experimental observations of wild type rodents, rodent models for neuropsychiatric diseases and diabetic mice [ 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%